Preliminary Study of Ground Level Ozone Nighttime Removal Process in an Urban Area (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
The depletion processes of nighhtime ground level Ozone (O3) concentrations in an urban area in Malaysia were evaluated. Annual monitoring records of O3 in Kota Bharu, Kelantan, were obtained from Department of Environment, Malaysia and separated into daytime and nighttime concentrations. In Malaysia, daytime starts from 7 a.m. until 7 p.m., and 7 p.m. to 7 a.m. is deemed as nighttime. The annual hourly average concentrations of O3 were 15.13±9.23 and 5.76±5.58 ppb for daytime and nighttime, respectively. The diurnal cycles of ground-level O3 concentrations suggests that a uni-modal peak occurs at 1 p.m. and high O3 concentrations was observed on December 2010 as a result of the higher rate of local photochemical production. Absence of photochemical reactions during nighttime identified as the main factor that contributed to low nighttime O3 concentrations. This study discovered that NO and NO2 play important role in O3 depletion process during nighttime. Results confirmed that high nighttime NO concentration enhanced further destruction of nighttime O3 concentrations.
Keywords: Depletion process; photochemical reaction; Kota Bharu; O3 nighttime chemistry